THE ROLE OF R2R3MYB TRANSCRIPTION FACTORS IN PLANT STRESS TOLERANCE - R. J. Xie; L. Zheng; L. Deng; S. L. He; S. L. Yi; Q. Lv; Y. Q. Zheng (Journal of Animal and Plant Sciences, 2014)
The plant-specific R2R3MYB proteins constitute a largest subfamily in MYB transcription factors and are widely involved in growth and developmental processes. In spite of their highly conserved DNA-binding domains, the biologic functions are strikingly varied across plant species. Recently, their roles in making plant more survivable under adverse environmental conditions including cold, drought, pathogen, salinity have received considerable attention. Nowadays, the R2R3MYBs in response to stresses, here termed as stress-responsive R2R3MYBs (SR-R2R3MYBs), were continuously identified from different plant species. This review mainly focused on the recent progresses in SR-R2R3MYBs gene structure, biological functions and their expression pattern under varied stresses. Additionally, we have also discussed the genetic relationship of SR-R2R3MYB proteins, and their role in integrating a diversity of pathways including metabolic, SOS, signal transduction pathways etc, with an aim to use them for crop improvement via transgenic technologies.
Keywords: R2R3MYB; transcription factor; stress signaling; biologic function; target gene